KANDUNGAN GIZI DAN DAYA TERIMA ROTI STREUSSEL KACANG GUDE (Cajanus Cajan) YANG KAYA KALIUM UNTUK PENDERITA HIPERTENSI - Fitriana, Isna Nur; Ratnaningsih, Nani; Lastariwati, Badraningsih (Jurnal Teknologi Hasil Pertanian, 2021)
Gude beans (Cajanus cajan) (L.) Millsp) or also called pigeon peas are a type of black legume that can be found in India, Asia and Africa. Pigeon peas are a source of protein, fiber, vitamins, and minerals, including potassium, but the utilization of pigeon peas for food, especially in the bakery, is still limited. This study aimed to determine the nutritional content of pigeon pea streussel bread through laboratory tests (proximate test and potassium content test) and public acceptance through panelists' preference test. This study used a R&D (Research and Development) with a 4D model (Define, Design, Development and Disseminate). Public acceptance  was conducted by 100 general public using a preference test form. Data analysis used descriptive statistics and paired sample t-test. The preference test of  gude streussel bread showed 4.09 (preferred). Nutritional content of pigeon pea streussel bread per 100 grams consisted of 51.3 grams of carbohydrates, 7.64 grams of protein, 10.36 grams of fat, 310.53 kcal of energy, and 188.79 mg of potassium. This research show that pigeon pea streussel bread can be consumed as a healthy bread for people with hypertension.